Analysis Of Production Costs In Determining Selling Prices Using The Full Costing Method At The Nuansa Porselen Indonesia Company - Nurul Ulfa; Edwin Zusrony; Kasih Purwantini (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
In today's world, with increasing competition among MSMEs, it is crucial to focus on competitiveness in product quality and price. This study aims to assess the calculation of the cost of goods manufactured to determine the appropriate selling price for Nuansa Porselen Indonesia Company. The full costing method is a technique for determining the cost of goods manufactured that includes all production costs, including raw material costs, direct labor, and factory overhead costs that include fixed and variable costs. The selling price is obtained from the cost of goods manufactured plus anticipated profits. This study was conducted using primary and secondary data. Primary data was obtained through direct observation and interviews with the company's financial manager, while secondary data was collected from several research journals and books. This study revealed that different calculations of the cost of goods manufactured and selling price have a direct impact on profitability.